Auditory and non-auditory hallucinations in first-episode psychosis: Differential associations with diverse clinical features. (August 2017) - Galletti, Chiara; Paolini, Enrico; Tortorella, Alfonso; Compton, Michael T.
Abstract: Data from 247 first-episode psychosis patients were used to explore associations between types of hallucinations and nine diverse clinical characteristics. Psychopathology was rated using the Scale for the Assessment of Positive Symptoms and Scale for the Assessment of Negative Symptoms (SANS). Childhood adversity was assessed with seven instruments; family history with an adapted version of the Family Interview for Genetic Studies ; age at onset of psychosis and duration of untreated psychosis (DUP) with the Symptom Onset in Schizophrenia inventory; and insight with the Birchwood Insight Scale . Both principal component analysis-derived Auditory and Non-Auditory Hallucinations were similarly associated with delusions of influence, negative affect delusions (jealousy and sin/guilt), interpersonal childhood abuse, DUP, and insight. However, the two hallucination domains had different associations with grandiose/religious, paranoid, and somatic delusions; SANS score; childhood violence exposure; cannabis use disorders; and cocaine/other drug use disorders. Neither Auditory nor Non-Auditory Hallucinations were associated with childhood neglect, age at onset, alcohol use disorders, family history, or mode of onset of psychosis. Findings support considering hallucinations not as a unitary psychopathological construct. They represent at least two domains and are correlated in different ways with diverse clinical variables. Highlights: Hallucinations are not homogeneous, but are composed of at least two types, auditory and non-auditory. These two types of hallucinations are correlated in different ways with diverse clinical variables. Findings may advance research by clarifying differential associations of auditory and non-auditory hallucinations.